2016
DOI: 10.1039/c6cp01419d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field actuated manipulation and transfer of oil droplets on a stable underwater superoleophobic surface

Abstract: L. (2016). Magnetic field actuated manipulation and transfer of oil droplets on a stable underwater superoleophobic surface. Physical Chemistry Chemical Physics, 18 (24), 16202-16207.Magnetic field actuated manipulation and transfer of oil droplets on a stable underwater superoleophobic surface AbstractThe transport of fluids at functional interfaces, driven by the external stimuli, is well established. The lossless transport of oil-based fluids under water remains a challenge, however, due to their high stick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Recently, Feng et al demonstrated a facile method for magnetic-field-driven manipulation and transport of oil-based magnetic fluids. 146 A ZnO nanorod array was grown on a glass substrate by a low-temperature hydrothermal method. The as-prepared ZnO nanoarrays consist of uniformly aligned nanorods with diameter of 150-250 nm and length of B6 mm.…”
Section: Magnetic Field Responsementioning
confidence: 99%
“…Recently, Feng et al demonstrated a facile method for magnetic-field-driven manipulation and transport of oil-based magnetic fluids. 146 A ZnO nanorod array was grown on a glass substrate by a low-temperature hydrothermal method. The as-prepared ZnO nanoarrays consist of uniformly aligned nanorods with diameter of 150-250 nm and length of B6 mm.…”
Section: Magnetic Field Responsementioning
confidence: 99%
“…For example, a series of bioinspired surfaces with micro/nanostructures show superoleophobic and low adhesive properties. In addition, stimulus responsive surfaces (e.g., magnetic, electric, and pH) exhibit tunable underwater oil adhesion. For instance, the nanostructured poly(acrylic acid) surface shows pH‐dependent oil‐adhesion with high adhesive force about 21.6 ”N at pH 1 and low adhesive force zero at pH 12 61b.…”
Section: Fundamental Models and Measuring Instruments Of Surface Adhementioning
confidence: 99%
“…In the past two decades, acoustic micro/nano manipulation methods [1][2][3] have shown tremendous potential applications in biomedical engineering [4,5], bioanalytical chemistry [6,7], material science [8,9], micro/nano fabrication [10,11], lab-on-a-chip (LOC) technology [12,13] and so forth. Compared to other physical micro/nano manipulation methods, such as optical methods [14,15], magnetic methods [16][17][18], mechanical methods [19,20], and dielectrophoretic (DEP) methods [21][22][23], acoustic micro/nano manipulation methods possess the merits such as simple fabrication, little selectivity to optical/electrical/magnetic properties of manipulated samples, and good compatibility with other LOC components [1,2]. The acoustic micro/nano manipulation devices can be divided into two major categories, i.e., surface acoustic wave (SAW)-based devices [24,25] and bulk acoustic wave (BAW)-based devices [1].…”
Section: Introductionmentioning
confidence: 99%